Digitalisasi Produktivitas Hasil Bumi dan Sertifikasi Halal Masyarakat Desa Labuan Kabupaten Tojo Una Una - Al Kautsar, Muhammad Syakir; Khoir, Fathul; Mahmudah, Nurul; Wahidah, Rochmatul (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2025)
This study explores the application of digitalization to enhance agricultural productivity and the implementation of halal certification in Labuan Village, Tojo Una-Una Regency. Despite the village’s significant agricultural potential, challenges such as limited digital technology usage and a lack of market access hinder the productivity and competitiveness of local products. Additionally, while there is strong awareness of halal certification, the complex process and associated costs prevent many producers from obtaining certification for their products.Using a qualitative approach with in-depth interviews, participatory observation, and document analysis, the study finds that digitalization can increase efficiency in production and distribution while expanding market reach. However, the community’s understanding of digital tools in the economic sector is still limited. Halal certification remains essential for market competitiveness, but barriers such as high costs and limited knowledge continue to impede its widespread adoption. The study concludes that to improve the productivity and market competitiveness of Labuan’s agricultural products, efforts should focus on providing training in digital technologies and supporting the halal certification process. Collaboration with the government, halal certifying bodies, and educational institutions is vital to overcoming these challenges. The integration of digitalization and halal certification is seen as a promising strategy to boost sustainable economic welfare in the village